Fracture behaviour of zirconia oxide filled unidirectional glass fibre reinforced plastic composites - Srivastava V.K. (My University, 2025)
Fracture behaviour of unidirectional E-glass fibre reinforced epoxy resin and Zirconia oxide hybrid composite and unidirectional E-glass fibre reinforced epoxy resin composite has been investigated. Experiments were conducted on a single edge notched specimen with different ratio of crack length to specimen width. The results show that the surface energy required for fracture is increased by adding the Zirconia oxide powder as a filler in unidirectional GRP composites. A fractography study also shows that the Zirconia oxide powder works as a barrier of the crack path. © 1988.